DEVELOPMENT OF TEACHING MATERIAL IN NARRATIVE TEXT BASED ON SPARKOL VIDEOSCRIBE AT MA RAUDHTUL HASANAH, MEDAN - ARI NINGSIH; HARIANTO II (State University of Medan, 2023)
The purpose of this development teaching the material research was to increase the students’ interest in X grade MAS PP Raudhatul Hasanah Medan. The development of teaching the material narrative text based on Sarkol VideoScribe adapts of the curriculum 2013 on third competency. The advantages of this development based on Sparkol VideoScribe such as: (1) Enhance teaching the material to be the most attractive and effective. (2) Can help to improve the interesting of students in reading and being active in the classroom. (3) Stimulate students’ attending of the lesson. (4) Increase students’ achievement in learning process. (5) Make the students are more exited. (6) The teachers enjoy and serve in learning atmosphere. This research and development approach will result in a finished product. The five-step ADDIE development paradigm is the one that was used. Analysis, design, development, implementation, and evaluation are the development measures. Before looking for the t-test result, the investigation establishes the results of normality and homogeneity. T-count is 16,2 and T-table is 1,6892 as a consequence of the calculation. Because t-count > t-table and there is a notable difference between learning outcomes prior to and following the use of teaching materials based on Sparkol VideoScribe's subtheme